Menjelajahi Opini Publik tentang Celebrity Fad Diets: Sentimen Twitter dan Analisis Netnografi: Exploring the Public Opinion on Celebrity Fad Diets: Twitter Sentiment and Netnographic Analysis - Kusuma, Ardyanisa Raihan; Putri, Sheila Amara; Rahmawati, Anisah Firdaus; Wijanarko, Mutiara Arsya; Arini, Shintia Yunita; Atmaka, Dominikus Raditya; Nor, Norfezah Md; Shahid, Nadiatul Syima Mohd; Jannah, Sa’idah Zahrotul (Universitas Airlangga, 2025)
Background: Celebrity fad diets have garnered significant attention in recent years. Celebrity diets often gain popularity through social media, particularly Twitter, where users engage in discussions, debates, and promotions of various diet trends. Objectives: To analyze Indonesian’s public sentiment surrounding celebrity fad diets on Twitter social media using netnographic from twitter. Methods: This research used a mixed-methods approach with both qualitative and quantitative methods to find the public sentiments of the 5 chosen diets. The data were obtained through snscrape from GitHub, a Python-based tool that enables users to access various types of Twitter data, such as user profiles, hashtags, live tweets, top tweets, users, single or threaded tweets, list posts, communities, and trends. Results: Positive sentiment was found to be more prevalent than negative sentiment over the years, and the number of tweets increased each year. Intermittent fasting emerged as the most discussed diet on social media, likely due to its resemblance to fasting practices observed by Indonesia's Muslim population. On the other hand, the Atkins diet was the least talked-about, possibly because of its complex nature. Conclusions: The prevalence of Ketogenic and Very Low-Calorie Diet discussions in the context of Indonesian and K-Pop culture underscores the need for a nuanced understanding of these diets and their potential implications for health. Future research should consider diverse data sources, expand sample sizes, and collaborate with experts to gain a more comprehensive understanding of public opinions on diets.